MYO1B promotes radioresistance in head and neck squamous cell carcinoma by regulating tumor stemness and DNA damage repair via the PI3K/AKT pathway - Yanan Li; Jiahao Liu; Zhen Wang; Yilei Zhang; Baiying Liu; Ling Chu (Cancer Cell International)
Abstract Head and Neck Squamous Cell Carcinoma is a prevalent malignancy characterized by high recurrence rates. While surgery remains the primary treatment, postoperative radiotherapy is essential for preventing tumor recurrence. However, the mechanisms driving radiotherapy resistance in HNSC remain largely unknown. With a multi-layered approach encompassing bioinformatics analysis, clinical tissue sample validation, in vitro and in vivo experiments, we discovered that MYO1B played a critical role in radiotherapy resistance of HNSC. Our findings underscored that MYO1B was significantly overexpressed in HNSC tissues and was associated with poor prognosis, particularly in patients undergoing radiotherapy. Functional investigations revealed that knockdown of MYO1B reduced the expression of stemness markers (SOX2, OCT4), decreased EMT-related protein levels, inhibited the phosphorylation of the key DNA damage repair protein ATM and increased sensitivity to radiotherapy. Mechanistically, knockdown of MYO1B inhibited the PI3K/AKT signaling pathway to reduce the expression of stemness-and DNA damage repair-related genes, and the use of an AKT activator reversed the observed reductions in tumor stemness and radiotherapy resistance. In vivo, MYO1B knockdown led to reduced tumor growth and enhanced radiotherapy sensitivity in a xenograft model. Clinical sample validation discovered that MYO1B was associated with disease-free survival, potentially due to higher tumor stemness and lower CD8 + cell infiltration. In summary, our study provides novel insights into the role of MYO1B in HNSC and highlights its potential as a therapeutic target for overcoming radiotherapy resistance. Graphical Abstract